Financial analysis of United Airlines Holdings, Inc. - Sidorenko, Konstantin (2022)
The topic of this bachelor thesis is the financial analysis of United Airlines Holdings, Inc. The first part of the work explains what financial analysis is and what sources of information are usually used to perform it. The second part gives information about the standard and specific methods used in the financial analysis of an airline. The third part presents the company. The fourth part explains the current situation in the American air travel market. The fifth examines the company’s financial reports for 2018-2021. The sixth part compares the company’s performance with competitors. As a result, it becomes clear that the company’s financial state in the short run is stable due to the high level of liquidity. However, in the long run, its financial well-being will mainly depend on external factors such as demand recovery, fuel prices, and interest rates’ development.